Experiment and Modeling of Smoke Ventilation in a Compartment using Coconut Husks as Solid Fuels - Beline Alianto; Gafero Prapila Rahim; Muhammad Agung Santoso; Nasruddin Nasruddin; Yulianto Sulistyo Nugroho (International Journal of Technology)
Modern architecture has become increasingly attractive and intriguing, with huge rooms and high ceilings. A 1:10 reduced-scale experimental compartment size 2.4 m x 1.6 m x 1.0 m has two floors with a mezzanine constructed. This study focuses on experimental and numerical using Fire Dynamic Simulator (FDS) studies on the transport of hot smoke produced by burning coconut husks as an actual fire source. A set of thermocouples were installed on the glass wall to measure the compartment temperature rise during the test. Laser beam sensors were utilized to measure the smoke obscuration. The experimental results were then compared with the numerical analysis study using FDS codes on a grid size of ?x = ?y = ?z = 5 cm. The results of tests indicate that the temperature rise in the compartment is mainly influenced by the air supply to the fuel, which varies the heat release rate. When compared, there are differences between the test data and the FDS prediction. FDS overestimates the rise in temperature during the early stages of smoke production compared to the test data. A performance-based design (PBD) can be considered when planning a fire safety system, primarily if solid fuels are used. In addition, coconut husks can be recommended as an alternative fire source for the hot-smoke test when solid fuel is considered. The emergence of white  smoke generated by coconut husks provide the repetition of experiments within the same compartment.